2022
DOI: 10.1002/ecs2.4087
|View full text |Cite
|
Sign up to set email alerts
|

Oyster abundance on subtidal reefs depends on predation, location, and experimental duration

Abstract: Predation affects community structure and functioning within marine habitats. Predator–prey interactions can change through space and time. Documenting how these interactions change is essential to improve our understanding of food web dynamics and to enhance our ability to manage preferred species. In this study, our goals were to determine whether the density of subtidal oysters (Crassostrea virginica) differed spatially by looking at three separate restored oyster sanctuaries within Pamlico Sound (North Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Our finding of relatively weak predator effects on oysters in the twocrab treatment is consistent with the hypothesis that intra-guild predation may partly release prey from predator control (Vance-Chalcraft et al, 2007). We speculate that within a confined area, these crabs may have interfered with or attacked one another, thereby weakening oyster predation (O'Connor et al, 2008;Byers et al, 2017;Geraldi et al, 2021). Oyster predation experiments from Byers et al (2017) (included in this meta-analysis) noted dead mud crabs in treatments with blue crabs suggesting that intraguild predation may have improved oyster survival.…”
Section: Predator Identity May Influence Predationsupporting
confidence: 84%
See 1 more Smart Citation
“…Our finding of relatively weak predator effects on oysters in the twocrab treatment is consistent with the hypothesis that intra-guild predation may partly release prey from predator control (Vance-Chalcraft et al, 2007). We speculate that within a confined area, these crabs may have interfered with or attacked one another, thereby weakening oyster predation (O'Connor et al, 2008;Byers et al, 2017;Geraldi et al, 2021). Oyster predation experiments from Byers et al (2017) (included in this meta-analysis) noted dead mud crabs in treatments with blue crabs suggesting that intraguild predation may have improved oyster survival.…”
Section: Predator Identity May Influence Predationsupporting
confidence: 84%
“…Moreover, contrary to the positive influences of predator richness on prey survivorship (McCoy et al, 2012;Griffin et al, 2013), we found no differences in oyster mortality effect sizes between the multi-taxon and either of the single-species predator treatments. This result could be explained by generalist predators preferring to feed on oysters (as opposed to other predator species within the enclosures; Byers et al, 2017;Geraldi et al, 2021), thereby strengthening the predator effect in the multitaxon predator treatment. A conch or drill was also included in most multi-predator taxon treatments (68% of effect sizes), further supporting the conclusion that gastropods are particularly effective in reducing oyster survival.…”
Section: Predator Identity May Influence Predationmentioning
confidence: 99%
“…Wong and Dowd (2021) explore how the functional traits of component species determine the level of secondary production in eelgrass communities. Alternatively, Geraldi et al (2022) examine the effects of top-down control on foundation species, in this case the influence of predation on oyster abundance on subtidal oyster reefs.…”
mentioning
confidence: 99%